Why great leaders use their intuitive intelligence for resounding success - Cholle, Francis (Henry Stewart Talks, 2021)
What Intuitive Intelligence can do for you in business, How to access and develop you own Intuitive Intelligence, iQ2™, SQUIRCLE™ model